Preparation and Application of Bifunctional Cellulose Aerogel Loaded with Anthocyanin Derived from Purple Corncob - Java, Soudeh; Aldoghaim, Timo; Costa , Miller (Journal of Green Energy and Environmental Engineering, 2025)
This study constructed dual-functional aerogels with pH-responsive colorimetry and antibacterial preservation by extracting cellulose and anthocyanins from purple corncobs and loading them with a cinnamon essential oil/β-cyclodextrin inclusion complex. The three-dimensional porous network structure endowed the aerogels with superior mechanical properties, achieving a compressive stress of 5.9 MPa at 90% strain. Compared to the control cellulose film material, the dual-functional aerogel exhibited faster pH responsiveness, with its steady-state color difference (ΔE) being approximately 1.25 times that of the film material. The aerogel loaded with the cinnamon oil/β-cyclodextrin inclusion complex showed a significantly slower decline in DPPH radical scavenging activity (12.48% over 60 hours) compared to the system with free essential oil (28.25% over 60 hours), representing a 55% improvement in sustained-release efficiency. Application experiments demonstrated that the bifunctional aerogel possessed more significant responsiveness and preservation effects for monitoring shrimp freshness. This research provides a theoretical foundation for developing materials for seafood freshness monitoring and preservation from agricultural waste.